High-temperature-resistant and high-salt-resistant polymer oil-displacing agent for oil exploitation and preparation method thereof

By introducing dynamic crosslinking agents into polymer oil flooding agents, a dynamic reconstructible molecular crosslinking network is formed, which solves the problem of insufficient thermal stability, salt resistance and shear stability of polymer oil flooding agents in high-temperature and high-salt reservoir environments, and achieves higher viscosity stability and oil flooding efficiency.

CN119798536AInactive Publication Date: 2025-04-11HUILONG ENERGY TECH (SHANDONG) CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510053119.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing polymer oil flooding agents have insufficient thermal stability, salt resistance and shear stability in high-temperature and high-salt reservoir environments, making it difficult to meet the needs of complex reservoir environments.

Method used

A dynamic crosslinking agent and functional polymer copolymer is adopted to form a dynamic reconstructible molecular crosslinking network through the synergistic effect of π-π stacking and hydrogen bonding to optimize the thermal stability, salt resistance and shear stability of the molecular chain.

Benefits of technology

It significantly improves the viscosity stability of polymer oil flooding agents in high temperature and high salt environments, solves the problems of thermal degradation and network collapse of traditional oil flooding agents under extreme reservoir conditions, and improves the stability of oil flooding efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119798536A_ABST
    Figure CN119798536A_ABST
Patent Text Reader

Abstract

The invention relates to the field of oil exploitation, discloses a high-temperature-resistant and high-salt-resistant polymer oil-displacing agent for oil exploitation, and discloses a preparation method of the high-temperature-resistant and high-salt-resistant polymer oil-displacing agent for oil exploitation, and the high-temperature-resistant and high-salt-resistant polymer oil-displacing agent for oil exploitation comprises the following components in percentage by weight: 5-15% of N-aryl acrylamide and 40-60% of 2-acrylamido-2-methylpropanesulfonic acid. Comprising the following steps: S1, dissolving N-aryl acrylamide, 2-acrylamido-2-methylpropanesulfonic acid, dodecyl acrylamide, acrylic acid and methacryloyloxyethyl trimethyl ammonium chloride into deionized water according to the weight percentage, and uniformly stirring. Through collaborative design of the dynamic cross-linking agent and the functional monomer, the polymer oil-displacing agent with high-temperature and high-salt adaptability is constructed, the polymer oil-displacing agent has excellent thermal stability, salt resistance and shear recovery capability, the problem of insufficient performance under extreme oil reservoir conditions in the prior art is effectively solved, and an efficient oil-displacing effect is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of oil production, in particular to a high-temperature resistant and high-salt polymer oil displacement agent for oil production and a preparation method thereof. Background Art

[0002] In oil production, polymer flooding technology has been widely used because it can effectively improve the recovery rate. However, as the development of oil reservoirs enters the middle and late stages, the environmental conditions of the remaining oil reservoirs become increasingly complex, and high-temperature and high-salinity oil reservoirs have become the main development targets. In such reservoirs, the reservoir temperature usually exceeds 120°C or even reaches above 150°C, the salinity is as high as 200,000 mg / L, and is accompanied by a large amount of hard ions (such as Ca 2+ Mg 2+ ) In the face of these harsh reservoir conditions, existing polymer flooding agents face significant deficiencies in performance.

[0003] Currently commonly used polyacrylamide (PAM) and its modified polymers show poor thermal stability in high temperature environments. Since its main chain structure is mainly composed of flexible CC bonds, thermal energy can cause the molecular chain to break or oxidatively degrade, resulting in a rapid decrease in solution viscosity. Although some studies have enhanced the rigidity of the molecular chain by introducing heat-resistant monomers (such as aromatic groups), a single main chain strengthening cannot completely solve the problem of thermal degradation. In complex reservoir environments, the breakage of molecular chains under high temperature conditions and the failure of cross-linking points are still inevitable, which directly weakens the performance sustainability of the oil displacement agent.

[0004] The salt shielding effect in a high-salt environment poses a greater challenge to the solubility and stretchability of polymer molecular chains. High concentrations of salt ions weaken the electrostatic repulsion between the charged groups in the molecular chain, causing the molecular chain to curl. At the same time, hard ions (such as Ca 2+ Mg 2+ ) may combine with the carboxyl or other functional groups in the polymer to form insoluble precipitates, further reducing the stability and viscosity of the solution. The traditional salt resistance modification method mainly improves the salt resistance by introducing strong hydrophilic groups (such as sulfonic acid groups). Although it has a certain effect under low-salt conditions, it cannot completely avoid the aggregation of molecular chains and performance degradation in high-salt environments with high hardness ion content.

[0005] In addition, during the oil displacement process, the polymer solution needs to withstand complex shear stress, especially in the high shear rate environment of the injection wellbore and porous media, the molecular chain is prone to breakage. Traditional chemical cross-linked polymers are difficult to rebuild the molecular network under high shear conditions due to the irreversible cross-linking points. This irreversible damage to the molecules directly leads to a decrease in the viscosity of the solution. Although the initial shear stability can be improved to a certain extent by increasing the cross-linking density, too high a cross-linking density will significantly reduce the flexibility of the molecular chain, reducing the fluidity and displacement efficiency of the solution.

[0006] More importantly, existing polymer technologies often focus on improving thermal stability, salt resistance or shear stability, but lack comprehensive consideration of the coordinated optimization of multifunctional properties. For example, some high-temperature resistant polymers have poor solubility under high-salt conditions, while salt-resistant modified polymers are prone to fracture or collapse in high-temperature or high-shear environments. This isolated modification method is difficult to meet the actual needs of complex reservoir environments.

[0007] Therefore, existing technologies have not yet achieved a comprehensive balance among thermal stability, salt resistance and shear stability when dealing with the development of high-temperature and high-salt oil reservoirs, and technical bottlenecks remain prominent. Summary of the invention

[0008] In view of the deficiencies in the prior art, the present invention provides a high-temperature and high-salt resistant polymer oil-displacing agent for oil recovery and a preparation method thereof, which solves the problems of insufficient thermal stability, salt resistance and shear stability of the polymer oil-displacing agent in a high-temperature and high-salt oil reservoir environment.

[0009] To achieve the above purpose, the present invention is implemented through the following technical scheme: a high-temperature and high-salt resistant polymer oil-displacing agent for petroleum exploitation comprises the following components by weight percentage: 5%-15% of N-aryl acrylamide, 40%-60% of 2-acrylamide-2-methylpropane sulfonic acid, 5%-10% of dodecyl acrylamide, 10%-15% of acrylic acid, 15%-25% of methacryloyloxyethyl trimethyl ammonium chloride and 1%-3% of a dynamic cross-linking agent.

[0010] Preferably, the dynamic crosslinking agent comprises a π-π crosslinking agent and a hydrogen bond enhancer, the π-π crosslinking agent accounts for 60%-70% of the total weight of the dynamic crosslinking agent, and the hydrogen bond enhancer accounts for 30%-40% of the total weight of the dynamic crosslinking agent.

[0011] Preferably, the N-aryl acrylamide is N-phenyl acrylamide.

[0012] Preferably, the π-π cross-linking agent is an anthraquinone derivative or a pyrrole compound, and the hydrogen bond enhancer is urea or trifluoroacetic acid.

[0013] Preferably, the dodecyl acrylamide is a reaction product of acrylamide and dodecyl bromide.

[0014] The preparation method of a high temperature resistant and high salt polymer oil displacement agent for oil extraction comprises the following steps:

[0015] S1, dissolving N-aryl acrylamide, 2-acrylamido-2-methylpropane sulfonic acid, dodecyl acrylamide, acrylic acid, and methacryloyloxyethyl trimethyl ammonium chloride in deionized water according to weight percentage, and stirring evenly;

[0016] S2, add ammonium persulfate and N,N,N ’ ,N , -tetramethylethylenediamine-based initiator system, with the total mass ratio of initiator to monomer controlled at 0.5%-1%;

[0017] S3, at a temperature of 60-70°C, add the dynamic crosslinker solution dropwise, and control the adding time to be 10-20 minutes;

[0018] S4, maintaining the reaction for 3-6 hours to obtain a polymer solution;

[0019] S5. Pour the reaction product into ethanol for precipitation, wash it, and freeze-dry it to obtain a polymer powder.

[0020] Preferably, the step of adding the dynamic crosslinking agent solution dropwise in S3 comprises the following steps:

[0021] S3.1, pre-dissolve the π-π cross-linking agent in dimethyl sulfoxide, the solution concentration is 50-100 mmol / L;

[0022] S3.2, dissolving the hydrogen bond enhancer in deionized water to form an aqueous solution with a concentration of 0.5%-2%;

[0023] S3.3, mixing the π-π crosslinking agent solution and the hydrogen bond enhancer solution in a ratio of 60%-70%:30%-40%;

[0024] S3.4, add the dynamic crosslinker solution evenly into the reaction system under stirring with a dropwise addition time of 10-20 min.

[0025] Preferably, the preparation of the initiator system in step S2 comprises the following steps:

[0026] S2.1, dissolving ammonium persulfate in deionized water to form an aqueous solution with a concentration of 0.5%-1%;

[0027] S2.2, N,N,N ’ ,N , -Tetramethylethylenediamine is dissolved in deionized water to form an aqueous solution with a concentration of 0.25%-0.7%;

[0028] S2.3. Before the reaction begins, mix the ammonium persulfate solution with N,N,N ’ ,N , -Tetramethylethylenediamine solution is mixed in a ratio of 1:0.5-0.7 to form a red redox initiator system;

[0029] S2.4. When the temperature of the reaction system rises to 50-60°C, the initiator system is added to the reaction system in batches, with a time interval of 5-10 minutes between each batch.

[0030] Preferably, the reaction conditions in step S4 include the following steps:

[0031] S4.1, adjusting the pH value of the reaction system to 6.5-7.5 by adding NaOH or HCl solution;

[0032] S4.2, control the reaction temperature at 60-70°C and maintain the constant temperature by a constant temperature water bath or an electric heating system;

[0033] S4.3, the reaction time is 3-6h, and the stirring is kept at a low speed in the later stage of the reaction, and the stirring speed is controlled at 100-300rpm to prevent the polymer from precipitating;

[0034] S4.4. Nitrogen protection is used during the reaction, with a nitrogen flow rate of 100-200 mL / min to prevent oxygen from entering the system and causing oxidative degradation.

[0035] Preferably, the freeze-drying process in step S5 comprises the following steps:

[0036] S5.1, washing the reaction product with deionized water and ethanol alternately after precipitation, the washing times are 3 times respectively;

[0037] S5.2. Place the washed product in a tray of a freeze dryer, and control the tray layer thickness to 3-5 mm;

[0038] S5.3, drying temperature is controlled at -30℃ to -20℃, vacuum degree is 0.1-0.3mbar;

[0039] S5.4. The freeze-drying time is 24-48 hours. After drying, the product is crushed into 100-200 mesh and sealed for storage.

[0040] The present invention provides a high temperature resistant and high salt polymer oil displacement agent for oil extraction and a preparation method thereof. It has the following beneficial effects:

[0041] 1. The present invention adopts a technical solution of copolymerization of dynamic cross-linking agent and functionalized polymer, and forms a dynamic and reconfigurable molecular cross-linking network based on π-π stacking and hydrogen bond synergistic effect. Compared with the single physical or chemical cross-linking solution in the prior art, it significantly improves the viscosity stability of polymer oil displacement agent in high temperature and high salt environment, and solves the problems of thermal degradation and network collapse of traditional oil displacement agent under extreme reservoir conditions.

[0042] 2. The present invention optimizes the thermal stability and shear resistance of the molecular chain by introducing N-aryl acrylamide and dodecyl acrylamide monomers, combining hydrophobic association and main chain heat resistance design. Compared with existing polyacrylamide oil-displacing agents, it avoids the problem of performance attenuation caused by molecular chain breakage, especially maintaining good solution viscosity under shear rate changes.

[0043] 3. The present invention adopts the molecular design of quaternary ammonium salt and sulfonic acid group, and utilizes the intramolecular charge shielding effect to achieve high salt, especially high hardness ions such as Ca 2+ Mg 2+ The stable stretching of the molecular chain is achieved in the environment. Compared with the traditional salt-resistant modified polymer solution, it avoids the problems of hard ion precipitation and molecular chain curling, thereby improving the solubility stability and long-term use effect.

[0044] 4. The present invention significantly improves the uniformity of molecular weight distribution and network structure integrity of the polymer by optimizing the initiator system and the dripping method of the dynamic cross-linking agent. Compared with the traditional one-step method or rapid polymerization process, it reduces the unevenness of molecular cross-linking, solves the problem of large fluctuations in product performance in the traditional process, and further enhances the stability of oil recovery efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 The present invention is a flow chart of the preparation method. DETAILED DESCRIPTION

[0046] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0047] Please see attached Figure 1 The embodiment of the present invention provides a high temperature and high salt resistant polymer oil displacement agent for oil production, which includes the following components by weight percentage: 5%-15% of N-aryl acrylamide, 40%-60% of 2-acrylamide-2-methylpropane sulfonic acid, 5%-10% of dodecyl acrylamide, 10%-15% of acrylic acid, 15%-25% of methacryloyloxyethyl trimethyl ammonium chloride and 1%-3% of a dynamic cross-linking agent.

[0048] The dynamic crosslinking agent comprises a π-π crosslinking agent and a hydrogen bond enhancer, wherein the π-π crosslinking agent accounts for 60%-70% of the total weight of the dynamic crosslinking agent, and the hydrogen bond enhancer accounts for 30%-40% of the total weight of the dynamic crosslinking agent.

[0049] N-arylacrylamide is N-phenylacrylamide.

[0050] The π-π cross-linking agent is an anthraquinone derivative or a pyrrole compound, and the hydrogen bond enhancer is urea or trifluoroacetic acid.

[0051] Dodecyl acrylamide is the reaction product of acrylamide and dodecyl bromide.

[0052] Specifically, N-aryl acrylamide (especially N-phenyl acrylamide) introduces rigid aromatic groups to increase the rigidity and heat resistance of the main chain of the molecule. The aromatic ring structure has high stability and can effectively inhibit the performance degradation of the polymer caused by thermal decomposition or chain breakage under high temperature conditions. At the same time, the rigid structure reduces the internal molecular movement of the molecular chain, which improves the overall heat resistance of the polymer, thereby ensuring that it maintains the integrity of the molecular chain and the viscosity of the solution at a reservoir temperature of 120-150°C.

[0053] AMPS is a strong hydrophilic monomer. Its sulfonic acid group (-SO 3 - ) has a high degree of hydrophilicity and strong charge interaction, which can significantly enhance the salt resistance of polymers in high-salt environments. The sulfonic acid group offsets the salt shielding effect through electrostatic repulsion, maintains the stretched state of the molecular chain, and avoids chain curling and solution viscosity reduction caused by high salt concentration. In addition, the sulfonic acid group and hard ions (such as Ca 2+ Mg 2+ ) has a weaker binding ability, which further reduces the possibility of precipitation and improves the solubility stability of the polymer.

[0054] Dodecyl acrylamide (C12AM) introduces long-chain alkyl hydrophobic groups and forms dynamic physical crosslinking points between molecules by hydrophobic association. These crosslinking points can stabilize the molecular network under high temperature and high shear conditions to prevent excessive separation or breakage of the molecular chains. The interaction of hydrophobic groups also enhances the viscosity-increasing properties of the solution, allowing the polymer to achieve efficient oil displacement at lower concentrations. In addition, C12AM avoids the solubility problem caused by excessive hydrophobic groups while ensuring hydrophobic association through synergistic effects with other hydrophilic monomers.

[0055] Acrylic acid (AA) provides carboxyl (-COOH) functional groups that react with hardness ions (such as Ca 2+ Mg 2+ ) to form a soluble complex, thus avoiding the precipitation induced by hard ions. In addition, the introduction of carboxyl groups has a certain regulatory effect on the solubility of the molecular chain and the overall network structure, so that the polymer still has good solubility under high salt conditions.

[0056] DMC provides quaternary ammonium groups (-N'R 3), which is positively charged and reacts with the sulfonic acid group (-SO 3 - ) forms an intramolecular charge shielding effect. This internal charge balance mechanism can offset the shielding effect of external high-salt ions, maintain the stretched state of the molecular chain, and further enhance the salt resistance of the polymer. At the same time, the positive charge also enhances the water solubility of the molecular chain and improves the solubility stability of the polymer in a high-salt environment.

[0057] π-π crosslinkers (such as anthraquinone derivatives or pyrrole compounds): π-π crosslinkers form dynamic physical crosslinking points between molecular chains through π-π stacking between aromatic rings. These crosslinking points are reversible and can automatically reconstruct under high temperature or shear conditions to maintain the integrity of the molecular network. Compared with traditional chemical crosslinking points, π-π stacking shows better dynamic response and stability under high temperature environment.

[0058] Hydrogen bond enhancers (such as urea or trifluoroacetic acid): Hydrogen bond enhancers further strengthen the stability of the dynamic cross-linked network through the formation of intermolecular hydrogen bonds. These hydrogen bonds are still reversible at high temperatures and can work synergistically with π-π stacking to enhance the cross-linking point density and recovery ability between molecular chains, thereby significantly improving the thermal stability and shear recovery properties of the polymer.

[0059] By optimizing the ratio of each monomer to the dynamic crosslinker, the present invention achieves the synergistic optimization of multiple properties. The high ratio of AMPS and DMC provides the molecular chain with strong salt resistance and good solubility; the combination of N-phenylacrylamide and C12AM constructs a stable molecular main chain and crosslinking network under high temperature environment; the introduction of the dynamic crosslinker further enhances the network's recovery ability and durable performance under high temperature and high shear conditions through π-π stacking and hydrogen bonding.

[0060] The preparation method of a high temperature resistant and high salt polymer oil displacement agent for oil extraction comprises the following steps:

[0061] S1, dissolving N-aryl acrylamide, 2-acrylamido-2-methylpropane sulfonic acid, dodecyl acrylamide, acrylic acid, and methacryloyloxyethyl trimethyl ammonium chloride in deionized water according to weight percentage, and stirring evenly;

[0062] S2, add ammonium persulfate and N,N,N ’ ,N , -tetramethylethylenediamine-based initiator system, with the total mass ratio of initiator to monomer controlled at 0.5%-1%;

[0063] S3, at a temperature of 60-70°C, add the dynamic crosslinker solution dropwise, and control the adding time to be 10-20 minutes;

[0064] S4, maintaining the reaction for 3-6 hours to obtain a polymer solution;

[0065] S5. Pour the reaction product into ethanol for precipitation, wash it, and freeze-dry it to obtain a polymer powder.

[0066] The addition of the dynamic crosslinker solution in S3 comprises the following steps:

[0067] S3.1, pre-dissolve the π-π cross-linking agent in dimethyl sulfoxide, the solution concentration is 50-100 mmol / L;

[0068] S3.2, dissolving the hydrogen bond enhancer in deionized water to form an aqueous solution with a concentration of 0.5%-2%;

[0069] S3.3, mixing the π-π crosslinking agent solution and the hydrogen bond enhancer solution in a ratio of 60%-70%:30%-40%;

[0070] S3.4, add the dynamic crosslinker solution evenly into the reaction system under stirring with a dropwise addition time of 10-20 min.

[0071] The preparation of the initiator system in step S2 comprises the following steps:

[0072] S2.1, dissolving ammonium persulfate in deionized water to form an aqueous solution with a concentration of 0.5%-1%;

[0073] S2.2, N,N,N ’ ,N , -Tetramethylethylenediamine is dissolved in deionized water to form an aqueous solution with a concentration of 0.25%-0.7%;

[0074] S2.3. Before the reaction begins, mix the ammonium persulfate solution with N,N,N ’ ,N , -Tetramethylethylenediamine solution is mixed in a ratio of 1:0.5-0.7 to form a red redox initiator system;

[0075] S2.4. When the temperature of the reaction system rises to 50-60°C, the initiator system is added to the reaction system in batches, with a time interval of 5-10 minutes between each batch.

[0076] The reaction conditions in step S4 include the following steps:

[0077] S4.1, adjusting the pH value of the reaction system to 6.5-7.5 by adding NaOH or HCl solution;

[0078] S4.2, control the reaction temperature at 60-70°C and maintain the constant temperature by a constant temperature water bath or an electric heating system;

[0079] S4.3, the reaction time is 3-6h, and the stirring is kept at a low speed in the later stage of the reaction, and the stirring speed is controlled at 100-300rpm to prevent the polymer from precipitating;

[0080] S4.4. Nitrogen protection is used during the reaction, with a nitrogen flow rate of 100-200 mL / min to prevent oxygen from entering the system and causing oxidative degradation.

[0081] The freeze drying process in step S5 comprises the following steps:

[0082] S5.1, washing the reaction product with deionized water and ethanol alternately after precipitation, the washing times are 3 times respectively;

[0083] S5.2. Place the washed product in a tray of a freeze dryer, and control the tray layer thickness to 3-5 mm;

[0084] S5.3, drying temperature is controlled at -30℃ to -20℃, vacuum degree is 0.1-0.3mbar;

[0085] S5.4. The freeze-drying time is 24-48 hours. After drying, the product is crushed into 100-200 mesh and sealed for storage.

[0086] Example 1: Preparation of high temperature and high salt resistant polymer oil displacement agent (optimization design of dynamic cross-linking agent)

[0087] Prepare monomer solution: Add N-phenylacrylamide (8 g), 2-acrylamido-2-methylpropanesulfonic acid (50 g), dodecylacrylamide (7 g), acrylic acid (13 g) and methacryloyloxyethyl trimethylammonium chloride (22 g) into 500 mL of deionized water. Stir at 200 rpm until the solution is completely clear. Keep the temperature at 25°C.

[0088] Initiator system configuration: Dissolve ammonium persulfate (APS, 0.8 g) in 20 mL of deionized water to make a 0.8% solution; ’ ,N , -Tetramethylethylenediamine (TEMED, 0.4 g) was dissolved in 10 mL of deionized water. The two solutions were mixed in a ratio of 1:0.5 to generate an initiator system.

[0089] Preparation of dynamic crosslinker solution: Dissolve anthraquinone derivative (2.1 g) in 20 mL of dimethyl sulfoxide (DMSO) at a concentration of 70 mmol / L. Dissolve urea (1.2 g) in 30 mL of deionized water at a concentration of 1%. Mix the two in a mass ratio of 65:35 and stir evenly to obtain a dynamic crosslinker solution.

[0090] Polymerization reaction: Add the initiator system to the monomer solution, and control the reaction temperature at 65°C. Slowly add the dynamic crosslinker solution under stirring (150rpm) for 15 minutes. Keep the reaction temperature constant and the reaction time is 4 hours. The nitrogen protection flow rate is 150mL / min.

[0091] Post-treatment: Pour the reaction product into 1L ice-cold ethanol for precipitation, take out the precipitate and wash it with deionized water for 3 times. Place the precipitate in a freeze dryer, and dry it under the conditions of -25°C, vacuum degree 0.2mbar, and time 36h. A white powder product is obtained.

[0092] Example 2: Preparation of hard ion resistant polymer oil displacement agent (strengthening intramolecular charge shielding)

[0093] Preparation of monomer solution: Weigh N-phenylacrylamide (10 g), 2-acrylamido-2-methylpropanesulfonic acid (55 g), dodecylacrylamide (6 g), acrylic acid (10 g) and methacryloyloxyethyltrimethylammonium chloride (19 g), add to 600 mL of deionized water and stir to dissolve. The stirring temperature is maintained at 20-25° C. and the stirring speed is 250 rpm.

[0094] Initiator preparation: Dissolve 0.6 g ammonium persulfate in 30 mL deionized water to make a 0.6% solution; ’ ,N , -Tetramethylethylenediamine was dissolved in 10 mL of water. Mixed in a mass ratio of 1:0.7 to prepare an initiator system.

[0095] Dynamic cross-linking agent configuration: Dissolve anthraquinone compound (2.5 g) in 30 mL DMSO to make a 80 mmol / L solution. Dissolve trifluoroacetic acid (1.5 g) in 40 mL water to form a 1.5% solution. Mix the two solutions in a ratio of 70:30 and stir evenly.

[0096] Polymerization reaction: The monomer solution was heated to 70°C. The initiator system was slowly added in batches with an interval of 5 minutes for a total of 3 additions. Under stirring conditions, the dynamic crosslinker solution was slowly dripped in, and the dripping time was controlled within 10 minutes. The reaction time was 3 hours, and the stirring speed was 200 rpm. Nitrogen protection was used throughout the process, with a flow rate of 100 mL / min.

[0097] Product recovery and drying: Pour the product into ice ethanol for precipitation, and take out the solid after standing for 15 minutes. Wash with deionized water and ethanol alternately for 3 times. Freeze drying conditions: -30℃, vacuum 0.1mbar, time 48h. Grind to 150 mesh to obtain white polymer powder.

[0098] Example 3: Preparation of a highly efficient shear-stable polymer oil-displacing agent

[0099] Preparation of monomer solution: Weigh N-phenylacrylamide (7 g), 2-acrylamido-2-methylpropanesulfonic acid (45 g), dodecylacrylamide (8 g), acrylic acid (14 g) and methacryloyloxyethyltrimethylammonium chloride (20 g), add to 500 mL of deionized water, stir until the solution is transparent, and control the temperature at 30°C.

[0100] Initiator system: ammonium persulfate (0.9 g) dissolved in 20 mL of water; N,N,N ’ ,N , -Tetramethylethylenediamine (0.6 g) was dissolved in 10 mL of water and mixed in a ratio of 1:0.6 for later use.

[0101] Dynamic cross-linking agent: Dissolve anthraquinone derivative (2 g) in 20 mL DMSO (concentration 100 mmol / L), and urea (1.8 g) in 30 mL water (concentration 2%). Mix the two solutions at a ratio of 60:40 and stir evenly.

[0102] Polymerization process: After the initiator is added to the monomer solution, the temperature is raised to 60°C. The stirring speed is adjusted to 150rpm, and the dynamic crosslinker solution is added dropwise, and the addition time is controlled within 20min. The reaction temperature remains unchanged and the reaction time is 5h. Nitrogen protection, flow rate 200mL / min.

[0103] Post-treatment: Pour the reactants into 1.2L cold ethanol and let stand for 20min. Wash with deionized water 3 times and with ethanol once. Freeze-drying conditions: -20℃, vacuum 0.3mbar, time 24h. A white powder product is obtained.

[0104] Example 4: Preparation of salt-resistant and stable polymer oil-displacing agent (under hard ion environment)

[0105] Preparation of monomer solution: Take N-phenylacrylamide (9 g), 2-acrylamido-2-methylpropanesulfonic acid (52 g), dodecylacrylamide (7 g), acrylic acid (11 g), and methacryloyloxyethyltrimethylammonium chloride (21 g), dissolve in 600 mL of deionized water, and stir until uniform and transparent.

[0106] Initiator system: Prepare 1% APS solution and 0.5% TEMED solution, and mix them in a ratio of 1:0.6. The solutions are mixed immediately before use.

[0107] Dynamic cross-linking agent: anthraquinone compound (1.8 g) was dissolved in 30 mL DMSO, trifluoroacetic acid (1.2 g) was dissolved in 40 mL water, mixed in a ratio of 70:30, and stirred thoroughly for use.

[0108] Polymerization reaction: The monomer solution was heated to 65°C and stirred continuously. After adding the initiator system, the dynamic crosslinker solution was gradually added dropwise for 15 minutes. The reaction time was 4 hours and the stirring speed was 150 rpm. Nitrogen protection was used throughout the process.

[0109] Drying: The product was precipitated with ice ethanol, washed twice with deionized water and once with ethanol. The freeze dryer temperature was -25°C, vacuum was 0.2 mbar, and the time was 36 h. A powder polymer was obtained.

[0110] Comparative Example 1: Adjustment of the ratio of the dynamic crosslinking agent (corresponding to Example 1)

[0111] The main difference: the ratio of π-π crosslinker to hydrogen bond enhancer is adjusted to 50:50.

[0112] Preparation process:

[0113] Monomer solution preparation: According to the monomer types and proportions in Example 1, N-phenylacrylamide, 2-acrylamido-2-methylpropanesulfonic acid, dodecylacrylamide, acrylic acid, and methacryloyloxyethyltrimethylammonium chloride were dissolved in deionized water and stirred to a transparent solution at a stirring speed of 200 rpm and a temperature of 25°C.

[0114] Initiator system: Referring to Example 1, the concentration and ratio of ammonium persulfate and TEMED remain unchanged.

[0115] Dynamic cross-linking agent preparation: Dissolve anthraquinone derivative (2.1 g) in 20 mL DMSO and urea (1.2 g) in 30 mL deionized water. When mixing the two solutions, adjust the mass ratio to 50:50, stir evenly and set aside.

[0116] Polymerization reaction: After the initiator system is added to the monomer solution, the dynamic crosslinker solution is added dropwise, and the addition time is controlled to be 15 minutes. The other conditions (temperature, stirring speed, reaction time, nitrogen protection) are consistent with Example 1.

[0117] Post-treatment: the same as in Example 1.

[0118] Comparative Example 2: No dynamic crosslinking agent was used (corresponding to Example 2)

[0119] The main difference: no dynamic cross-linking agent is added, and a conventional monomer copolymerization system is used.

[0120] Preparation process:

[0121] Monomer solution preparation: According to the monomer types and proportions in Example 2, N-phenylacrylamide, 2-acrylamido-2-methylpropanesulfonic acid, dodecylacrylamide, acrylic acid, and methacryloyloxyethyltrimethylammonium chloride were dissolved in deionized water with a stirring speed of 250 rpm and a temperature of 25°C.

[0122] Initiator system: Referring to Example 2, the concentration and ratio of ammonium persulfate and TEMED remain unchanged.

[0123] Polymerization reaction: After the initiator system was added to the monomer solution, the dynamic crosslinker solution was not added dropwise. Other reaction conditions (temperature 65° C., stirring speed 200 rpm, reaction time 3 h, nitrogen protection 100 mL / min) were consistent with Example 2.

[0124] Post-treatment: The precipitation and freeze-drying conditions of Example 2 were followed.

[0125] Comparative Example 3: N-phenylacrylamide is replaced by acrylamide (corresponding to Example 3)

[0126] Main difference: N-phenylacrylamide is replaced by acrylamide, and the monomer design is adjusted to adjust the heat resistance.

[0127] Preparation process:

[0128] Monomer solution preparation: According to the monomer ratio of Example 3, acrylamide (7 g) was used to replace N-phenylacrylamide, and 2-acrylamido-2-methylpropanesulfonic acid, dodecylacrylamide, acrylic acid, and methacryloyloxyethyltrimethylammonium chloride were dissolved in 500 mL of deionized water, and stirred to a transparent solution at a stirring speed of 150 rpm.

[0129] Initiator system: refer to the initiator ratio of Example 3.

[0130] Dynamic cross-linking agent configuration: The type and ratio of the dynamic cross-linking agent are consistent with those in Example 3.

[0131] Polymerization reaction: After the initiator system is added to the monomer solution, the dynamic crosslinker is slowly added dropwise for 20 min. The reaction temperature is 60°C, the reaction time is 5 h, and the nitrogen protection flow rate is 200 mL / min.

[0132] Post-treatment: The precipitation and freeze-drying conditions of Example 3 were followed.

[0133] Comparative Example 4: No introduction of dodecyl acrylamide (corresponding to Example 4)

[0134] Main difference: hydrophobic associating monomers are removed and the polymer has no physical cross-linking points.

[0135] Preparation process:

[0136] Monomer solution preparation: N-phenylacrylamide (9 g), 2-acrylamido-2-methylpropanesulfonic acid (52 g), acrylic acid (11 g), and methacryloyloxyethyltrimethylammonium chloride (21 g) were dissolved in 600 mL of deionized water according to the monomer ratio of Example 4. Dodecyl acrylamide was removed, and other operations remained unchanged.

[0137] Initiator system: refer to the initiator ratio of Example 4.

[0138] Dynamic cross-linking agent configuration: The type and ratio of the dynamic cross-linking agent are consistent with those in Example 4.

[0139] Polymerization reaction: After the initiator system is added to the monomer solution, the dynamic crosslinker is slowly added dropwise for 15 minutes. The reaction temperature is 65°C, the reaction time is 4 hours, the stirring speed is 150 rpm, and nitrogen protection is used throughout the process.

[0140] Post-treatment: Process according to the precipitation and freeze-drying conditions of Example 4.

[0141] Comparative Example 5: Dynamic crosslinking agent replaced by chemical crosslinking agent

[0142] The main difference is that the dynamic crosslinker is replaced by the chemical crosslinker N,N , -Methylenebisacrylamide (MBA) replacement.

[0143] Preparation process:

[0144] Monomer solution preparation: According to the monomer ratio of Example 1, N-phenylacrylamide, 2-acrylamido-2-methylpropanesulfonic acid, dodecylacrylamide, acrylic acid, and methacryloyloxyethyltrimethylammonium chloride were dissolved in deionized water, and the stirring speed was 200 rpm.

[0145] Cross-linking agent configuration: 1% N,N , - Methylenebisacrylamide (MBA) solution, with a concentration of 0.2%-0.5%, is directly added to the reaction system instead of the dynamic cross-linking agent.

[0146] Polymerization reaction: The temperature (65°C), stirring speed, reaction time (4h) and nitrogen protection were followed in Example 1.

[0147] Post-treatment: same as in Example 1.

[0148] Experiment 1: Temperature resistance test

[0149] Experimental purpose: To verify the viscosity retention ability of the polymer oil-displacing agent of the present invention under high temperature (150°C), test its thermal stability, and compare it with the comparative example.

[0150] Experimental steps:

[0151] Sample solution preparation:

[0152] According to the formulations in Example 1 and Example 3, polymer powders were weighed respectively to prepare 0.5% (mass percentage) aqueous solutions, which were stirred until the solutions were completely clear.

[0153] Comparative Example 2 (without dynamic crosslinking agent) and Comparative Example 3 (N-phenylacrylamide was replaced by acrylamide) were prepared in the same manner.

[0154] Initial viscosity determination:

[0155] The sample solution was placed in a constant temperature water bath at 25 °C and the initial viscosity was measured using a rotational rheometer (Anton Paar MCR102) with a shear rate set to 50 s -1 . Record the initial viscosity value.

[0156] High temperature treatment: Transfer the sample solution to a sealed reaction bottle, place it in a 150°C thermostat, and let it stand for 72 hours.

[0157] Final viscosity measurement: After 72 hours, the solution was taken out and cooled to 25°C. The viscosity value was measured again using the rotational rheometer under the same conditions as the initial measurement.

[0158] Viscosity retention calculation:

[0159] The viscosity retention rate is calculated according to the following formula:

[0160]

[0161] Experimental data:

[0162] Table 1: Viscosity retention of samples at high temperature (150°C)

[0163] Sample No. Initial viscosity (mPa·s) Viscosity after 72h (mPa·s) Viscosity retention rate (%) Example 1 42.3 35.6 84.2 Example 3 46.7 38.4 82.2 Comparative Example 2 38.1 12.6 33.1 Comparative Example 3 40.2 18.3 45.5

[0164] Experimental summary:

[0165] Molecular stability at high temperatures is crucial. Examples 1 and 3 of the present invention show excellent viscosity retention. This is due to the introduction of a dynamic cross-linking agent. The π-π stacking effect in the dynamic cross-linking agent forms a reversible molecular network. Even at a high temperature of 150°C, the cross-linking points between molecules can still be reconstructed through non-covalent interactions. In contrast, due to the lack of a dynamic cross-linking agent in Comparative Example 2, there is a lack of a stable network structure between the molecular chains, and thermal decomposition and molecular chain breakage are inevitable, resulting in a rapid decrease in viscosity.

[0166] In addition, the present invention introduces N-phenylacrylamide in the monomer design, making the polymer main chain structure more rigid and significantly improving the high temperature resistance. This is particularly evident in Example 3. The acrylamide alternative adopted in Comparative Example 3 has a more flexible molecular structure, and the main chain is easy to break or degrade at high temperatures. The network lacks rigid skeleton support, so its viscosity retention rate is only 45.5%, which is much lower than that of the embodiment.

[0167] The heat resistance of the molecular chain not only depends on the rigidity of the main chain, but is also closely related to the hydrophobic association. The dodecyl acrylamide in the embodiment provides additional physical crosslinking points through long-chain hydrophobic groups. These crosslinking points can still maintain the network structure under high temperature conditions, thereby achieving a stable viscosity-increasing effect. However, due to the lack of hydrophobic groups or dynamic crosslinking agents in Comparative Examples 2 and 3, network collapse becomes an inevitable problem, which is directly reflected in its extremely low viscosity retention rate.

[0168] Experiment 2: Salt tolerance test

[0169] Experimental purpose: To test the polymer flooding agent in high salt (200,000 mg / LNaCl + 10,000 mg / LCa 2+ ) conditions, verifying the salt resistance of the polymer of the present invention.

[0170] Experimental steps:

[0171] Sample configuration:

[0172] According to the formulations of Example 2 and Example 4, sample solutions with a concentration of 0.5% (mass percentage) were prepared respectively.

[0173] The samples of Comparative Example 1 (dynamic crosslinking agent ratio adjustment) and Comparative Example 4 (no introduction of dodecyl acrylamide) were also prepared into solutions with a concentration of 0.5%.

[0174] Use high salt solution (200,000 mg / L NaCl + 10,000 mg / L Ca 2+ ) instead of deionized water to dissolve, and stir until the solution is transparent or uniformly turbid.

[0175] Initial viscosity determination: Place the sample solution in a 25°C constant temperature water bath and use a rotational rheometer to determine the initial viscosity. The shear rate is set to 50s -1 , record the initial viscosity value.

[0176] High-salt stability treatment: The sample solution was transferred to an 80°C thermostat and left to stand for 72 hours to simulate long-term storage conditions in a high-salt environment.

[0177] Transmittance determination: The transmittance of the solution was determined using a UV-visible spectrophotometer with the detection wavelength set at 600 nm. The decrease in transmittance reflects the dissolution stability.

[0178] Final viscosity measurement: After 72 hours, take out the sample and cool it to 25°C. Measure its viscosity value again, compare it with the initial viscosity, and calculate the viscosity retention rate.

[0179] Experimental data:

[0180] Table 2: High salt (200,000 mg / L NaCl + 10,000 mg / L Ca 2+ ) changes in sample viscosity retention and transmittance under the conditions

[0181]

[0182]

[0183] Experimental summary:

[0184] When the salt concentration is high, the molecular chains of many polymers will begin to curl. The present invention establishes a flexible and stable network between the molecular chains by introducing a dynamic cross-linking agent. These networks rely on π-π stacking and hydrophobic effects to maintain the extensibility of the molecular chains. In Examples 2 and 4, the dynamic cross-linking agent has an obvious effect. In contrast, after the dynamic cross-linking agent ratio in Comparative Example 1 is adjusted, the effect is not good, the network structure is loose, and the chain collapses under high salt conditions.

[0185] In the embodiment, N-phenylacrylamide also contributes greatly to the salt resistance. It makes the main chain more stable, combines the sulfonic acid group and the quaternary ammonium salt group, not only prevents chain breakage, but also effectively reduces the hardness of ions such as Ca 2+ Mg 2+ The possibility of this "trouble molecule" getting entangled with the polymer chain. Comparative Example 4 removes dodecyl acrylamide, lacks hydrophobic association, and reduces the physical cross-linking points between molecular chains. In this case, the salt shielding effect directly deforms the chain, and the transmittance drops rapidly.

[0186] In addition, the decrease in transmittance is a very intuitive comparison point in a high-salt environment. In the embodiment, the solution transmittance changes very little, indicating that the solubility and dispersibility of the molecules in the solution are very stable. The turbidity of the comparative example increases significantly, indicating that the molecules have begun to aggregate or even precipitate, further verifying the advantage of the dynamic cross-linked network of the present invention in salt tolerance.

[0187] Experiment 3: Shear stability test

[0188] Experimental purpose: To evaluate the viscosity retention ability of the polymer oil displacement agent at high shear rate and verify the contribution of the dynamic cross-linking network of the present invention to shear stability.

[0189] Experimental steps:

[0190] Sample configuration:

[0191] The polymer powders of Example 1, Example 3, Comparative Example 2 (without dynamic crosslinking agent), and Comparative Example 5 (dynamic crosslinking agent replaced by chemical crosslinking agent) were prepared into aqueous solutions with a concentration of 1%.

[0192] Magnetic stirring was used during solution preparation, and the dissolution time was controlled at 1 h until the solution was transparent or uniform.

[0193] Initial viscosity determination: The initial viscosity was measured using a rotational rheometer (model: Anton Paar MCR102) with a shear rate set to 10 s -1 , keep the constant temperature at 25℃.

[0194] Shear Test:

[0195] The shear rate was increased from 10 s -1 Gradually increase to 1000s -1 , the test time is 60 seconds.

[0196] The viscosity of the solution was measured immediately after the high shear rate ended. The test conditions were constant and the temperature was kept at 25°C.

[0197] Viscosity retention calculation:

[0198] The viscosity retention rate is calculated by the following formula:

[0199]

[0200] Repeat the experiment:

[0201] Each group of samples was repeated 3 times, and the average value was taken as the final result.

[0202] Experimental data:

[0203] Table 3: High shear rate (1000s -1 ) sample viscosity retention rate under the condition

[0204]

[0205]

[0206] Experimental summary:

[0207] High shear rate is a severe test for polymer solutions, especially for traditional polymers, whose viscosity often drops rapidly. The present invention forms a reversible molecular network by introducing a dynamic crosslinker. The performance of Example 1 and Example 3 shows that the π-π stacking effect in the dynamic crosslinker can still quickly restore the crosslinking points of the molecular chain after shearing. This dynamic reconstruction ability allows the viscosity retention rate to be maintained at more than 85%, while in the comparative examples, there is a lack of dynamic crosslinking or chemical crosslinking, the network recovery is significantly insufficient, and the viscosity is almost halved after shearing.

[0208] Under high shear conditions, the hydrophobic association of dodecyl acrylamide in the examples also plays an important role. The long-chain alkyl groups form physical crosslinking points between molecules, making the molecular network structure of the solution more compact. This is particularly evident in Comparative Example 2. In the absence of a dynamic crosslinking agent, the interaction between the molecular chains is weakened, and the crosslinking points are difficult to recover, resulting in a viscosity retention rate of the solution after shearing of only 46.4%. This shows that the hydrophobic association design of the present invention provides great support for shear stability.

[0209] As for comparative example 5, in which a chemical crosslinker replaces a dynamic crosslinker, although the initial viscosity is high, the chemical crosslinking points are difficult to recover at high shear rates, the shearing action causes the molecular chains to break permanently, and the network structure cannot be repaired. The present invention, through the synergistic effect of the dynamic crosslinker, achieves dynamic reconstruction of the molecular network while avoiding the defect of the rigid chemical crosslinking network structure. This is also directly reflected in the significant difference in viscosity after shearing.

[0210] Experiment 4: Oil displacement performance test

[0211] Experimental purpose: To simulate high-temperature and high-salinity oil reservoir conditions, test the oil displacement effect of the polymer oil displacement agent, verify the practical application value of the present invention, and compare it with the comparative example.

[0212] Experimental steps:

[0213] Core preparation:

[0214] Natural sandstone cores were selected with dimensions of 50 mm (length) x 25 mm (diameter). The porosity was determined to be 24%-26% and the permeability was 450-500 mD.

[0215] The core was saturated with simulated brine (mass concentration 200,000 mg / L NaCl + 10,000 mg / L Ca) under vacuum pump. 2+ ), and let it stand for 24 hours to ensure complete saturation.

[0216] Sample configuration:

[0217] The polymer solutions of Example 1, Example 2, Comparative Example 1 (dynamic crosslinking agent ratio adjustment), and Comparative Example 3 (N-phenylacrylamide replaced by acrylamide) were prepared, and the concentrations were all 1%.

[0218] The solution was stirred and dissolved and then allowed to stand for 6 h to ensure uniform distribution.

[0219] Experimental setup:

[0220] A standard core flooding experimental apparatus was used, connected to a thermostat (set at 120°C), a pressure sensor and an injection pump.

[0221] Simulated brine was used as the displacement fluid and pre-saturation fluid.

[0222] Experimental process:

[0223] Phase 1: Pre-injection with simulated saline

[0224] Simulated brine was injected into the core at a flow rate of 2 mL / min until the crude oil was completely displaced, and the initial water saturation was determined.

[0225] Phase 2: Injection of crude oil

[0226] Inject simulated crude oil (viscosity 20 mPa·s) until the oil saturation is stable, and record the data.

[0227] Stage 3: Injection of polymer solution

[0228] The injection fluid was replaced with a polymer solution and injected at a rate of 2 mL / min until the pressure was stable. The changes in displacement pressure and recovery factor were recorded.

[0229] Recovery factor calculation:

[0230] The oil recovery factor is calculated according to the following formula:

[0231]

[0232] Repeat the experiment:

[0233] Two cores were tested for each group of samples and the average value was taken.

[0234] Experimental data:

[0235] Table 4: Test results of polymer flooding agent flooding performance

[0236] Sample No. Initial oil saturation (%) Displacement pressure (MPa) Oil recovery rate (%) Example 1 65.4 2.1 56.2 Example 2 63.9 2.3 58.5 Comparative Example 1 66.1 1.8 42.3 Comparative Example 3 64.7 2.0 47.8

[0237] Experimental summary:

[0238] The oil displacement experiment is the last link of performance verification, which directly reflects the actual effect of the polymer in the reservoir environment. Examples 1 and 2 of the present invention show a high oil recovery rate. The core of this performance lies in the design of the dynamic cross-linker. The dynamic cross-linker not only increases the viscosity of the solution, but also keeps the molecular network stable under high salt and high temperature. π-π stacking and hydrophobic association form a reversible molecular network, which can respond quickly to changes in fluid flow pressure even during the displacement process and maintain an effective displacement effect.

[0239] The molecular chain optimization design in the embodiment is also crucial. The rigid main chain structure provided by N-phenylacrylamide ensures that the molecule is not easy to break at high temperature, and the synergistic effect with other monomers further enhances the salt resistance. In contrast, after the dynamic cross-linking agent ratio in Comparative Example 1 was adjusted, the reconstruction ability of the network structure was significantly reduced, and the recovery rate was greatly affected. In the absence of sufficient cross-linking points, the fluid viscosity in the oil recovery process is insufficient, and the high permeability channel cannot be effectively blocked, resulting in a significant reduction in oil recovery efficiency.

[0240] Looking at the situation of Comparative Example 3, after acrylamide was used to replace N-phenylacrylamide, the heat resistance of the molecular chain was directly damaged. Under high temperature environment, molecular chain breakage and performance degradation are inevitable. This result intuitively reflects the importance of rigid monomers. It can be clearly seen from the tests of the embodiments that the improvements in the dynamic crosslinker and molecular design of the present invention, combined with the synergy of multiple mechanisms, successfully solved the key problems in high-temperature and high-salinity oil reservoirs.

[0241] Experiment 5: Molecular network characterization test

[0242] Experimental purpose: To characterize the dynamic stability of polymer molecular networks through dynamic mechanical analysis and verify the performance of dynamic cross-linked networks under different temperature and frequency conditions.

[0243] Experimental steps:

[0244] Sample preparation:

[0245] Example 1, Example 3, Comparative Example 2 (without dynamic crosslinking agent), and Comparative Example 5 (dynamic crosslinking agent replaced by chemical crosslinking agent) were prepared into hydrogels with a concentration of 1%, and solid samples were formed by freeze drying. The samples were cut into rectangular specimens of 20×10×2 mm to avoid irregular edges affecting the test.

[0246] Dynamic Mechanical Analysis:

[0247] A dynamic mechanical analyzer (DMA, model: TAI Instruments Q800) was used. The sample was clamped on the fixture and the mode was selected as the tensile mode.

[0248] Test frequency range: 1rad / s to 100rad / s.

[0249] Temperature range: 30℃ to 150℃, heating rate 5℃ / min. Record storage modulus (G , ) and loss modulus (G ,, ) changes with temperature and frequency.

[0250] Data Record:

[0251] Comparative Example and Comparative Example Storage modulus (G , ) at different temperatures reflects the stability of the molecular network.

[0252] Calculate the loss factor (tanδ = G ,, / G , ), analyzing the viscoelastic changes of molecular networks at high temperatures.

[0253] Repeat the experiment:

[0254] Each group of samples was tested 3 times and the average value was taken.

[0255] Experimental data:

[0256] Table 5: Storage modulus of different samples (G , ) Changes with temperature

[0257]

[0258] Experimental summary:

[0259] Storage modulus (G , ) directly reflects the strength and stability of the molecular network. At high temperatures, the crosslinking points of the polymer molecular chains will gradually lose stability, and a decrease in modulus is inevitable. However, the experimental results show that Examples 1 and 3 can still maintain a relatively high storage modulus at 150°C. This is due to the introduction of dynamic crosslinkers, especially π-π stacking and hydrophobic association. These two non-covalent interactions have good dynamic reconstruction capabilities at high temperatures, allowing the network to recover repeatedly.

[0260] The performance of Comparative Example 2 is very typical. The molecular network without dynamic crosslinking agent support has a significant decrease in modulus after the temperature rises to 80°C, and almost loses its mechanical strength at 150°C. This shows that dynamic crosslinking plays an irreplaceable role in the stability of the molecular network. Without dynamic crosslinking points, the connection between molecular chains cannot withstand structural damage in a thermal environment by chemical bonds alone.

[0261] Although chemical crosslinkers have a slight advantage in initial modulus, they lack dynamic recovery ability. In Comparative Example 5, the modulus retention rate of the network structure at 150°C is only 46.4%, indicating that chemical crosslinking points are easily broken and irreversible at high temperatures. The present invention introduces more flexible physical crosslinking points between molecular chains through the design of dynamic crosslinking agents. They can respond quickly to chain movement under high temperature conditions, maintain the integrity of the network, and provide better elastic behavior, which is particularly prominent in the stability of storage modulus and loss factor.

[0262] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A high temperature resistant and high salt polymer oil displacement agent for oil production, characterized in that: The invention comprises the following components by weight percentage: 5%-15% of N-aryl acrylamide, 40%-60% of 2-acrylamide-2-methylpropane sulfonic acid, 5%-10% of dodecyl acrylamide, 10%-15% of acrylic acid, 15%-25% of methacryloyloxyethyl trimethyl ammonium chloride and 1%-3% of a dynamic cross-linking agent.

2. The high temperature resistant and high salt polymer oil displacement agent for oil production according to claim 1, characterized in that: The dynamic crosslinking agent comprises a π-π crosslinking agent and a hydrogen bond enhancer, wherein the π-π crosslinking agent accounts for 60%-70% of the total weight of the dynamic crosslinking agent, and the hydrogen bond enhancer accounts for 30%-40% of the total weight of the dynamic crosslinking agent.

3. The high temperature resistant and high salt polymer oil displacement agent for oil production according to claim 1, characterized in that: The N-aryl acrylamide is N-phenyl acrylamide.

4. The high temperature resistant and high salt polymer oil displacement agent for oil production according to claim 2, characterized in that: The π-π cross-linking agent is an anthraquinone derivative or a pyrrole compound, and the hydrogen bond enhancer is urea or trifluoroacetic acid.

5. The high temperature and high salt resistant polymer oil displacement agent for oil production according to claim 1, characterized in that: The dodecyl acrylamide is a reaction product of acrylamide and dodecyl bromide.

6. A method for preparing a high temperature resistant and high salt polymer oil displacement agent for oil production, characterized in that: The following steps are involved: S1, dissolving N-aryl acrylamide, 2-acrylamido-2-methylpropane sulfonic acid, dodecyl acrylamide, acrylic acid, and methacryloyloxyethyl trimethyl ammonium chloride in deionized water according to weight percentage, and stirring evenly; S2, add ammonium persulfate and N,N,N ’ ,N , -tetramethylethylenediamine-based initiator system, with the total mass ratio of initiator to monomer controlled at 0.5%-1%; S3, at a temperature of 60-70°C, add the dynamic crosslinker solution dropwise, and control the adding time to be 10-20 minutes; S4, maintaining the reaction for 3-6 hours to obtain a polymer solution; S5. Pour the reaction product into ethanol for precipitation, wash it, and freeze-dry it to obtain a polymer powder.

7. The method for preparing the high temperature resistant and high salt polymer oil displacement agent for oil production according to claim 6, characterized in that: The dropwise addition of the dynamic crosslinking agent solution in S3 comprises the following steps: S3.1, pre-dissolve the π-π cross-linking agent in dimethyl sulfoxide, the solution concentration is 50-100 mmol / L; S3.2, dissolving the hydrogen bond enhancer in deionized water to form an aqueous solution with a concentration of 0.5%-2%; S3.3, mixing the π-π crosslinking agent solution and the hydrogen bond enhancer solution in a ratio of 60%-70%:30%-40%; S3.4, add the dynamic crosslinker solution evenly into the reaction system under stirring with a dropwise addition time of 10-20 min.

8. The method for preparing the high temperature resistant and high salt polymer oil displacement agent for petroleum exploitation according to claim 6, characterized in that: The preparation of the initiator system in step S2 comprises the following steps: S2.1, dissolving ammonium persulfate in deionized water to form an aqueous solution with a concentration of 0.5%-1%; S2.

2. N,N,N ’ ,N , -Tetramethylethylenediamine is dissolved in deionized water to form an aqueous solution with a concentration of 0.25%-0.7%; S2.

3. Before the reaction begins, mix the ammonium persulfate solution with N,N,N ’ ,N , -Tetramethylethylenediamine solution is mixed in a ratio of 1:0.5-0.7 to form a red redox initiator system; S2.

4. When the temperature of the reaction system rises to 50-60°C, the initiator system is added to the reaction system in batches, with a time interval of 5-10 minutes between each batch.

9. The method for preparing the high temperature resistant and high salt polymer oil displacement agent for petroleum exploitation according to claim 6, characterized in that: The reaction conditions in the step S4 include the following steps: S4.1, adjusting the pH value of the reaction system to 6.5-7.5 by adding NaOH or HCl solution; S4.2, control the reaction temperature at 60-70°C and maintain the constant temperature by a constant temperature water bath or an electric heating system; S4.3, the reaction time is 3-6h, and the stirring is kept at a low speed in the later stage of the reaction, and the stirring speed is controlled at 100-300rpm to prevent the polymer from precipitating; S4.

4. Nitrogen protection is used during the reaction, with a nitrogen flow rate of 100-200 mL / min to prevent oxygen from entering the system and causing oxidative degradation.

10. The method for preparing the high temperature resistant and high salt polymer oil displacement agent for petroleum exploitation according to claim 6, characterized in that: The freeze drying process in step S5 comprises the following steps: S5.1, washing the reaction product with deionized water and ethanol alternately after precipitation, the washing times are 3 times respectively; S5.

2. Place the washed product in a freeze dryer tray, and control the tray layer thickness to 3-5 mm; S5.3, drying temperature is controlled at -30℃ to -20℃, vacuum degree is 0.1-0.3mbar; S5.

4. The freeze-drying time is 24-48 hours. After drying, the product is crushed into 100-200 mesh and sealed for storage.

Citation Information

Cited By

  • High-molecular polymer demulsifier as well as preparation method and application thereof

    CN121248836A